Association between different dietary patterns and eating disorders and periodontal diseases - Maísa Casarin; Taciane Menezes da Silveira; Beatriz Bezerra; Flavia Q. Pirih; Natália Marcumini Pola (Frontiers Media S.A., 2023)
Periodontal diseases is a highly prevalent chronic condition regulated by the host immune response to pathogenic bacterial colonization on the teeth surfaces. Nutrition is a critical component in the modulation of the immune system, hence the importance of a balanced diet. With the understanding of how dietary intake composition affects various health outcomes, nutrient diversity has been reported as a modifiable risk factor for periodontal disease. Eating disorders and different dietary patterns can be associated with periodontal diseases. In this sense, balanced and healthy nutrition plays a major role in maintaining the symbiosis between oral microbiota and periodontal health. Therefore, this review seeks to report the associations found in the literature between high- or low-fat/sodium/sugar, eating disorders and periodontal diseases. It was found that some dietary patterns such as high carbohydrate/sugar, high fat, and low fiber intake may be associated with periodontal disease. In addition, the presence of eating disorders can negatively impact patients' oral health and it is related to the development of several complications, including periodontal diseases. In both situations, nutritional and vitamin deficiencies can aggravate the periodontal condition. However, the relationship between periodontal disease, dietary patterns, and eating disorders still needs more scientific support to be well established, mainly in the sense of pointing out a protective relationship between both.